1991
DOI: 10.1182/blood.v78.2.364.bloodjournal782364
|View full text |Cite
|
Sign up to set email alerts
|

DEGR-factor Xa blocks disseminated intravascular coagulation initiated by Escherichia coli without preventing shock or organ damage

Abstract: One of the aims of research in the area of thrombosis has been to design an effective anticoagulant that would function in a predictable and direct manner. In evaluating the role of coagulation in sepsis we used factor Xa blocked in the active center with [5-(dimethylamino)1- naphthalenesulfonyl]-glutamylglycylarginyl+ ++ chloromethyl ketone (DEGR-Xa). We infused 1 mg/kg of DEGR-Xa together with LD100 concentrations of Escherichia coli (4 x 10(10) organisms/kg) into five baboons. As controls, we infused E coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
55
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 2 publications
(2 reference statements)
0
55
1
1
Order By: Relevance
“…In addition, Carr and colleagues (4) have shown that infusion of recombinant-TFPI (rTFPI) reduces the mortality, as well as the coagulation abnormalities in baboons injected with lethal doses of Escherichia coli . Since the lethal effect of E. coli is not reduced by attenuation of coagulopathic responses (5), anticoagulant effects of TFPI appear not to contribute to its reduction of lethal effects in the septic baboon model. Acute respiratory distress syndrome (ARDS) is a serious complication in septic patients (6).…”
mentioning
confidence: 92%
“…In addition, Carr and colleagues (4) have shown that infusion of recombinant-TFPI (rTFPI) reduces the mortality, as well as the coagulation abnormalities in baboons injected with lethal doses of Escherichia coli . Since the lethal effect of E. coli is not reduced by attenuation of coagulopathic responses (5), anticoagulant effects of TFPI appear not to contribute to its reduction of lethal effects in the septic baboon model. Acute respiratory distress syndrome (ARDS) is a serious complication in septic patients (6).…”
mentioning
confidence: 92%
“…However, administration of recombinant human APC (rhAPC) has been shown to restore levels of PC to improve patient survival (Bernard et al, 2001a). This beneficial effect associated with rhAPC is not completely explained by the antithrombotic and profibrinolytic effects of APC, because blocking the coagulation pathway with heparin or activated factor X (FXa) did not improve the survival rate in endotoxemic baboons (Coalson et al, 1978;Taylor et al, 1991) and administration of other anticoagulants, such as anti-thrombin III and tissue factor pathway inhibitors, have not shown a comparable improvement in patient survival (Warren et al, 2001;Abraham et al, 2003). Furthermore, experiments in a mouse model of sepsis using a mutant APC lacking anticoagulant activity, demonstrated that the mutated APC was still able to maintain a cytoprotective effect (Kerschen et al, 2007).…”
mentioning
confidence: 99%
“…Here, we confirmed these findings and extended them under conditions in which andexanet was co-administered with hEGR-Xa in a rat anticoagulation model. EGR-Xa is a well-characterized, catalytically inactive, human FXa molecule that competes with FXa for assembly into the prothrombinase complex with high affinity, and has a potent anticoagulant effect [10,11,16]. The addition of a 10-fold excess of andexanet to hEGR-Xa had no additive effect on prolongation of clotting times, suggesting that at the concentrations used in this study, andexanet did not compete with native FXa for binding on the phospholipid surface to form a prothrombinase complex, and thus had no anticoagulant effect.…”
Section: Discussionmentioning
confidence: 99%